Cosa significa abitare in periferia? - Giuseppe Scandurra (EtnoAntropologia, 2018)
Over the last fifteen years, if we focus on the northern outskirts of Bologna and study the settlement patterns of the foreign citizens in order to read the territory, the dialectic South / North seems to take on more importance than the duality center / periphery.  In recent years, however, there’s  a new trend not readable through merely quantitative data and that is the formation of areas - blocks, housing estates – strongly affected by the presence of “second generation” immigrants. I began to wonder: how did the municipal area change in recent years and how should we call these suburbs?